Legal framework for protection against domestic violence in Lithuania - Matulevičiūtė, Laima; Grinkevič, Joanna (Vilnius University Open Series, 2024)
This course work analyzes the concept of domestic violence and the ways in which it manifests itself. Court practices and legal doctrine are used for this. The concept of close environment and violence is discussed. The latter is divided into subtypes which are separately detailed and their concepts are presented as they are understood in the specified sources. In addition, this work discusses the competence of pre-trial investigation officers, its regulation until 1st of July, 2023 and after this date. The main difference from 1st of July, 2023 is that the institution of the violence warrant came into effect, the purpose of which is to effectively protect the victim of domestic violence. Also, preventive and auxiliary measures of protection against domestic violence applied by different European countries were examined. Finally, the work discusses the perspectives of the violence warrant, justifies its need, discusses its shortcomings and offers suggestions on how its regulation could be improved.
Keywords: Law on Protection against Domestic Violence; domestic violence; protection from violence order; pre-trial investigation officers